Dear Daughter - Szirtes, András (Szirtes, András, 2004)
Duration: 01:22:00 "I cut the umbilical cord. When I took it in my arms tears rolled down my cheeks. Its mother was afraid to hold it so I was the first to bathe it. Then… it peed on me… And what did it say first? Yes, you heard it right: Daddy!It soon turned out it was as stubborn as me. Stages of becoming a human: climbing off the tree, and then lifting front limbs up… This film shows the euphoria of this experience. The script was written by ”Life” with a capital ”L”. Jean-Luc Godard, whom I respect as my mentor, was once asked how to make a film: ”It’s simple. All you have to know is when to switch the camera on, and when to switch it off”. Well, I took his words seriously and worked and lived according to this for the next seven years. In "Dear Daughter," a story built on itself, the most difficult thing was how to guard successfully the semblance of naturalness against a consciously designed plan. It should be as if everything develops spontaneously as the spool revolves in the camera. During the seven weeks of filming I did not look at the material. It was all in my head at nights, and when my main protagonist was asleep I had to think up the location and events of the shoot for the following day. My cameraman and friend Sándor Kardos helped me a great deal in this. "Dear Daughter" traces a person’s life from birth to the age of seven. This was the right title for my film instead of ”Big Brother”, the popular reality show these days." [director András Szirtes]